Perspektif Konstitusi tentang Pemberdayaan dan Penjaminan Atas Hak-Hak Perempuan - Dedi Sumanto; Abdul Latif; Andi Mardiana (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2013)
Human Rights, is aset of rights inherent in the nature and existence of every human beings which must be respected, and protected by the state, law, government, and every person, for the respect and protection of human dignity. Constitutional rights of citizens which include human rights and citizens' rights are guaranteed by the1945 Constitution which bound to every citizen of Indonesia. These rights are recognized and guaranteed to every citizen for men and women. The empowerment and quarantee should have the same opportunity to determine the option by rejecting any inferior asumsption and erasing differences based on gender is legalized by law. Therefore, women themselves recognize the importance of raising the issue of women rights as one of the types of human rights that must be recognized and guaranteed.